Urban food waste generation and sustainable management strategies: a case study of Nonthaburi Municipality, Thailand - Pantakan Choochote; Nuta Supakata (Scientific Reports)
Abstract Although increasing global attention has been devoted to food waste management, there is still a critical research gap in understanding waste patterns and developing contextualized solutions for rapidly urbanizing areas in developing nations, where waste management infrastructure lags behind urban expansion. Using stratified random sampling of 244 sources encompassing markets, restaurants, institutions, and residential areas in Nonthaburi Municipality, Thailand, this study identified and characterized three distinct food waste categories: edible surplus food (FW1), food preparation waste, including spoiled items and bones (FW2), and postconsumption remnants (FW3). Analysis of the waste proportion patterns revealed that FW2 predominated (65.53%), followed by FW3 (32.55%) and FW1 (1.92%). Fresh markets constituted the principal source of waste generation (294.1 ± 42.3 kg/day), yielding a significantly greater quantity than private markets (117.61 ± 35.7 kg/day) and supermarkets (20.4 ± 12.8 kg/day). Statistical analyses revealed significant variations (p < 0.05) in food waste proportions across source categories. Given these findings and local infrastructure limitations, this study proposes a systematic, three-phase implementation strategy: (1) Immediate application of FW3 conversion to aquaculture feed, with an estimated food waste diversion potential of 10.72 ± 7.15 tons/day; (2) medium-term establishment of FW1 redistribution programs, which target 1.92% of total waste identified as edible surplus food, with a projected daily redistribution capacity of 0.153 ± 0.11 tons; and (3) long-term development of FW2 biofertilizer facilities, with an estimated food waste diversion potential of 52.62 ± 18.95 tons/day. This integrated approach simultaneously advances multiple sustainable development goals and establishes a replicable framework for sustainable food waste management in rapidly urbanizing regions of developing nations. The findings provide essential guidance for policy-makers and urban planners in implementing resource-efficient waste management systems.